1985
DOI: 10.1111/j.1745-4557.1985.tb00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Times, Cooking Losses and Energy Used for Cooking Lamb Roasts

Abstract: Cooking times and losses were monitored during cooking of ten each of eight kinds of lamb roasts. Roasts were cooked (163OC oven, not preheated) to be rare (6OoC), medium (7OOC) or well done (77OC). Cooking times and cooking losses significantly increased with increasing degrees of doneness. Cooking time recommendations were made based on the data I n a second study, cooking times, cooking losses and energy consumption were monitored during cooking o f 100 each of boneless legs and boneless shoulder roasts. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…College of Agricultural Engineering Sciences, University of Sulaimani, seven semi-expert panellists were involved to evaluate the meat of the four groups. The evaluation included colour, flavour, juiciness, tenderness and overall acceptability (palatability) for longissimus dorsi (LD) muscle according to Griffin et al (1985). The frozen meat sample from each group was thawed for 24 hr.…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…College of Agricultural Engineering Sciences, University of Sulaimani, seven semi-expert panellists were involved to evaluate the meat of the four groups. The evaluation included colour, flavour, juiciness, tenderness and overall acceptability (palatability) for longissimus dorsi (LD) muscle according to Griffin et al (1985). The frozen meat sample from each group was thawed for 24 hr.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…in a refrigerator at 4ºC. The sample was then split into equal parts and wrapped in aluminum foil and oven-roasted for 45 minutes at 125°C (Griffin et al, 1985).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…This relationship has been studied empirically. In a particular study, around 240 roasts were cooked to calculate the ideal cooking time [30]. Table 3, which was adapted from [30], shows the recommended cooking times for the corresponding lamb roasts.…”
Section: Cooking Methods (Roasting/rotisserie)mentioning
confidence: 99%
“…In a particular study, around 240 roasts were cooked to calculate the ideal cooking time [30]. Table 3, which was adapted from [30], shows the recommended cooking times for the corresponding lamb roasts. The findings suggested that the lamb roasts increased in doneness with time.…”
Section: Cooking Methods (Roasting/rotisserie)mentioning
confidence: 99%
“…The samples were tested for tenderness, juiciness, flavor and overall acceptability by rating on a 7 points hedonic scale. The thawed samples were cut into equal pieces, wrapped individually in aluminum foil and oven roasted at 125°C for 45 min (Griffin et al, 1985; as cited by Abdel et al, 2010). Immediately after roasting, the samples were cut into uniform size pieces and held in a food warmer until served.…”
Section: Sensory Evaluation For Eating Quality Of Meatmentioning
confidence: 99%